BEYOND THE BORDER WAR: NEW PERSPECTIVES ON SOUTHERN AFRICA’S LATE COLD WAR CONFLICTS/EDITED BY G. BAINES AND P. VALE - Liebenberg, Ian (Scientia Militaria - South African Journal of Military Studies, 2011)
Namibia became independent after decades of struggle when the apartheid government accepted UN Resolution 435. In Windhoek the flag of the occupier finally made way for one heralding a rising sun. Peace returned to Namibia and Namibia to the Namibians. South Africa had withdrawn from Angola after years of intimate involvement. Jonas Savimbi, leader of the rebel movement Unita and a former proxy of South Africa, continued the civil war for another dozen years. The landmines remained. In many towns and villages in Angola the maimed and the wounded are still to be seen.